2019
DOI: 10.5964/jspp.v7i2.1104
|View full text |Cite
|
Sign up to set email alerts
|

Why do first and second-generation young migrants volunteer? The Migrant Volunteerism Motivation Model (MVMM)

Abstract: The following study aims at inquiring into the motivations behind young migrants’ volunteerism in civic organizations in Italy, namely in starting and maintaining their engagement (preliminary vs. maintenance phase). The term “young migrants” refers to first and second generation of migrants who deal with two challenges: the transition to adulthood and the acquisition of a cultural identity. We conducted semi-structured interviews with 37 Sub-Saharan young migrants living in Italy (18-32 years old), 19 of firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Finally, this study confirms that young people are attentive and sensitive to social issues, as elsewhere described (Alfieri et al, 2019 ) and have developed a concern for community.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, this study confirms that young people are attentive and sensitive to social issues, as elsewhere described (Alfieri et al, 2019 ) and have developed a concern for community.…”
Section: Discussionsupporting
confidence: 89%
“….] We're not just like our parents, who came here from abroad: we know how to dress like them, maybe how to speak their language, but we're little suited to expressing only that culture (Nora,female,30) As observed in the scholarly debate, second-generation immigrants have to cope with the transition to adulthood and the formation of belonging under the influence of their origin and the mainstream culture of arrival (Alfieri, Marzana, and Damia 2019). Against this backdrop, positionings located on the cusp between native and foreign subjectivities 'escape' traditional frameworks of identity and belonging (Ríos-Rojas 2011).…”
Section: Volunteerism and Visibility: On How Volunteering Helps To Ge...mentioning
confidence: 99%
“…In the sharing of religious, moral, and behavioral values and the provision of material, financial, social, psychological, and emotional support, Wang (2017) has identified six essential forms of immigrant associations: self-help organizations, ethnic cultural organizations, ethnic-oriented religious organizations, hometown associations, immigrant non-profit organizations, and shared interest groups. As research in the United States of America (USA) and Western European context has shown, forms of immigrant participation and associational arrangements vary by ethnic and immigrant status and migrant generation (see Alfieri et al, 2019; Kawashima-Ginsberg and Kirby, 2009; Marcelo et al, 2007). For instance, Marcelo et al (2007) identified Asians as more civically engaged than other ethnic groups in the USA, with youth volunteering more than adults.…”
Section: Theoretical Backgroundmentioning
confidence: 99%